The role of the Ombudsman's Office in the promotion, practice and dissemination of fundamental rights in Ecuador - Rodríguez Camacho, María Enriqueta (Revista Universidad de Guayaquil, 2024)
The safeguarding and protection of human rights is one of the main objectives of the Ombudsman's Office and is the body in charge of the promotion and sponsorship of citizens. However, when investigating this institution within Ecuador, various limitations are reflected that have influenced the fulfillment of the rights of Ecuadorians. Therefore, this study is based on the analysis of the role of the Ombudsman's Office in the promotion, exercise and dissemination of fundamental rights in Ecuador, with the purpose of establishing whether the functions developed by this institution favor the rights of the Ecuadorian citizens. The development of this research was developed from a legal doctrine analysis, under a cross-sectional, descriptive study and the use of an empirical method of documentary and bibliographic analysis, synthesized and examined a group of international research and descriptors developed during the period 2016 -2021. The results made it possible to verify that there are currently inconsistencies that demonstrate ineffective actions undertaken by this institution, concluding that the actions carried out by this institution do not provide a timely solution to the majority of the requirements requested by citizens. A situation that coincides with world reports on human rights, which reflects its concern about the persistent violation of human rights in Ecuador.
Keywords: Civil liability; legal institution; contractual and non-contractual civil liability